Analisis Pengaruh Nilai Ekspor, Utang Luar Negeri dan Nilai Tukar Mata Uang Terhadap Pertumbuhan Ekonomi Indonesia Periode 2010–2024 - Taufikur Rahman; Baiq Saripta Wijimulawiani; Ali Akbar Hidayat (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this study is to examine how Indonesia's economic growth is influenced by export values, foreign debt, and exchange rates over the period of 2010–2024. The main issue investigated is the uncertainty of the contribution of external factors such as exports and foreign debt in promoting economic growth, as well as the volatility of exchange rates that potentially creates a dilemma between export competitiveness and inflation risk. A quantitative research method is applied using secondary data from the Central Bureau of Statistics (BPS), Bank Indonesia, and other official sources in the form of time series data from 2010 to 2024. Multiple linear regression analysis using Eviews 13 shows that foreign debt has a negative and significant impact on Indonesia's economic growth, while export values and exchange rates have a positive but insignificant impact on Indonesia's economic growth. The coefficient of determination (Adj. R²) of 41.4% indicates that other variables outside the model also influence economic growth. These findings confirm that foreign debt becomes a major inhibiting factor due to the risk of debt overhang and unproductive allocation, while exports are not yet optimal due to dependence on primary commodities and global price fluctuations or exchange rate volatility. The results of this study provide new perspectives in evaluating the interaction of external and internal factors in the context of Indonesia's economic recovery. This study recommends export diversification, productivity-based debt management, and exchange rate stabilization through integrated policies.